An examination of the ethical implications of violence in Abrahamic religions for Nigerian commonwealth (2018)
Religion is a terrain that guarantees communion between the object of worship and adherents. This implies that religious beliefs and activities or practices of a particular religion should not be forced on adherents of other religions. But the contrary is the case in many climes, especially in Nigeria, where people flout the principles of religious pluralism. Often times, such disregard for tolerance of adherents of other religions in a diverse society, breeds violence that leads to monumental loss of lives and property thereby impinging negatively on Nigerian Commonwealth. Therefore, this research is highly interested, firstly, in the examination of the veracity of the claim by adherents of Christianity and Islam that their religions epitomise peace and secondly examine the factors that trigger religious violence vis-a-vis the ethical implications of such religious induced violence on the societal psyche. This becomes imperative in order to critically address its effects with a view to reducing inter and intra religious conflicts that have engulfed Nigeria in particular and some nations of the world in general. In view of the fact that this research falls within the ambit of contextual study, phenomenological method will be employed to carry out the primary investigation; while literary works of scholars shall be consulted in order to elucidate information on the subject matter.